Radiologic response as a prognostic factor in advanced hepatocellular carcinoma with macroscopic vascular invasion after transarterial chemoembolization and radiotherapy - Jinhong Jung; Ji Hyeon Joo; So Yeon Kim; Jin Hyoung Kim; Jonggi Choi; Danbi Lee; Ju Hyun Shim; Kang Mo Kim; Young-Suk Lim; Han Chu Lee; Jin-hong Park; Sang Min Yoon (Liver Cancer, 2021)
Introduction: We evaluated the radiologic response rate of combined transarterial chemoembolization (TACE) plus radiotherapy (RT) in treatment-naïve patients with liver-confined hepatocellular carcinoma (HCC) with macroscopic vascular invasion (MVI) and analyzed its clinical importance in overall survival (OS) outcomes. Methods: Patients who were treated with TACE plus RT as a first-line treatment for HCC with MVI between January 2010 and December 2015 were retrospectively reviewed. Radiologic response was assessed according to the modified Response Evaluation Criteria in Solid Tumors (mRECIST) at 2- and 4-months after completion of RT. Landmark analysis at 2- and 4-months and time-dependent Cox regression analysis using response as a time-dependent covariate were performed for univariable and multivariable analyses. Results: The 2-month landmark analysis included 427 patients, and the 4-month landmark analysis included 355 patients after excluding patients without imaging studies for response evaluation at 4 months. Radiologic responses were observed in 210 (49.2%) patients at 2 months and 181 (51.8%) at 4 months. In multivariable analyses, radiologic response was identified as an independent prognosticator for OS at 2 months (median OS: responders, 23.1 months vs. non-responders, 8.0 months; hazard ratio [HR], 3.194; P < 0.001) and 4 months (median OS: responders, 26.5 months vs. non-responders, 9.3 months; HR, 4.534; P < 0.001). Conclusion: Radiologic response assessed by mRECIST was a significant prognostic factor for OS in patients with advanced-stage HCC showing MVI treated with combined TACE plus RT.